Enhancing Business Intelligence with Explainable AI: Evaluating Transparency, Interpretability, and User Trust - Aji Jayaloka; Alfa Ryano Yohannis (Politeknik Pertanian Negeri Samarinda, 2025)
The integration of Artificial Intelligence (AI) into Business Intelligence (BI) systems has significantly advanced data analysis and decision-making capabilities. However, the inherent